Disentangling tau and brain atrophy cluster heterogeneity across the Alzheimer's disease continuum. Issue 1 (23rd May 2022) - Toledo, Jon B.; Liu, Hangfan; Grothe, Michel J.; Rashid, Tanweer; Launer, Lenore; Shaw, Leslie M.; Snoussi, Haykel; Heckbert, Susan; Weiner, Michael; Trojanwoski, John Q.; Seshadri, Sudha; Habes, Mohamad; et al.
Abstract: Introduction: Neuroimaging heterogeneity in dementia has been examined using single modalities. We evaluated the associations of magnetic resonance imaging (MRI) atrophy and flortaucipir positron emission tomography (PET) clusters across the Alzheimer's disease (AD) spectrum. Methods: We included 496 Alzheimer's Disease Neuroimaging Initiative participants with brain MRI, flortaucipir PET scan, and amyloid beta biomarker measures obtained. We applied a novel robust collaborative clustering (RCC) approach on the MRI and flortaucipir PET scans. We derived indices for AD‐like (SPARE‐AD index) and brain age (SPARE‐BA) atrophy. Results: We identified four tau (I–IV) and three atrophy clusters. Tau clusters were associated with the apolipoprotein E genotype. Atrophy clusters were associated with white matter hyperintensity volumes. Only the hippocampal sparing atrophy cluster showed a specific association with brain aging imaging index. Tau clusters presented stronger clinical associations than atrophy clusters. Tau and atrophy clusters were partially associated. Conclusions: Each neuroimaging modality captured different aspects of brain aging, genetics, vascular changes, and neurodegeneration leading to individual multimodal phenotyping.